2012
DOI: 10.1590/s1808-86942012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Zumbido em indivíduos sem perda auditiva e sua relação com a disfunção temporomandibular

Abstract: Research has shown that dysfunction of the temporomandibular joint is often associated with tinnitus.Aim: to characterize tinnitus in individuals with normal hearing and search for a possible relationship with Temporomandibular Disorders (TMD). Study design: prospective and cross-sectional. Materials and Methods: the participants included 20 adults of both genders with tinnitus and normal hearing thresholds on audiometry. We studied tinnitus psychoacoustic characteristics and employed the checklist of TMD sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
1
1
0
8
Order By: Relevance
“…Regarding the laterality of tinnitus, we verified 56.65% of bilateral and 43.35% of unilateral complaints, being 23.3% in the right ear and 20% in the left ear, similarly to the studies that reported 70%; 67% and 60% of patients with bilateral tinnitus and 30%; 33% and 25% with unilateral tinnitus, respectively 13,23,25 . However, other authors have reported higher incidence of unilateral tinnitus (left ear) (65%) in individuals with normal pure tone audiometryl 22 .…”
supporting
confidence: 89%
“…Regarding the laterality of tinnitus, we verified 56.65% of bilateral and 43.35% of unilateral complaints, being 23.3% in the right ear and 20% in the left ear, similarly to the studies that reported 70%; 67% and 60% of patients with bilateral tinnitus and 30%; 33% and 25% with unilateral tinnitus, respectively 13,23,25 . However, other authors have reported higher incidence of unilateral tinnitus (left ear) (65%) in individuals with normal pure tone audiometryl 22 .…”
supporting
confidence: 89%
“…A relação entre a dor da DTM e o zumbido é relacionada devido à proximidade anatômica entre a ATM e o sistema auditivo, além dos pontos-gatilho, em especial nos músculos esternocleidomastoideo e masseter, que quando estimulados provocam dor no local e à distância 4 ; assim, a formação de pontos algógenos nesses músculos pode provocar irradiação para a orelha, gerando zumbido [11][12] .…”
Section: Discussionunclassified
“…A ocorrência de queixas auditivas em indivíduos com DTM foi analisada por meio do registro das Emissões Otoacústicas Evocadas por Estímulo Transiente (EOET) cujos limiares auditivos se encontram dentro dos padrões de normalidade 2,[11][12] . Este estudo embora não tenha confirmado a alteração no mecanismo de amplificação coclear causada pela DTM, salientou que o fonoaudiólogo, em função da alta incidência de queixas auditivas deve considerar a hipótese de ocorrência de alterações na ATM e realizar os encaminhamentos necessários, mesmo na ausência de perda auditiva, objetivando a efetivação do diagnóstico e tratamento adequados.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Acoustic symptoms within the joints, manifested as popping and cracking sounds, are an evidence of the lack of coordination between the articular head TMJ articular discs during mandible movements [2]. Patients with TMD characterize their tinnitus as acute, continuous, sporadic, of short duration, moderate intensity, and that generally did not interfere with their daily activities [36]. Otolaryngological symptoms are a less common group of dysfunction symptoms, including sudden hearing impairment or loss, ear plugging sensation and earache, sore and burning throat, difficulties in swallowing, and vertigo [3,4,6].…”
Section: Tmd Diagnosis and Complementary Testsmentioning
confidence: 99%